Factors Influencing Perceptions Of University Students Towards Internet Recruitment - Ming, Wendy Yen Teoh; Sy Cha , Tan; Siong , Choy Chong (Asian Academy of Management (AAM), 2013)
This study aims to determine the factors that influence the perceptions of university students towards Internet recruitment. Data were collected from 250 university students from five universities through self-reported questionnaires that were e-mailed to them. The results indicate that factors such as user friendliness, information provision, and website usability are significantly related to the perceptions of university students towards Internet recruitment. Amongst the three factors, information provision appears to be the strongest predictor. It can be concluded that Internet recruitment will continue to gain prominence, and employers must pay considerable attention to their online recruitment information, appearance, features, and functions if they wish to attract the right job candidates.